Extracorporeal photopheresis in the treatment of acute and chronic graft-versus-host disease: A position statement from the Turkish Society of Apheresis (TSA) - Kaynar, Leylagül; Tekgündüz, Emre; Kozanoğlu, İlknur; Özkan, Hasan Atilla; Aksu, Salih; Özkalemkaş, Fahir; Demirkan, Fatih (Pergamon-Elsevier Science Ltd, 2022)
Graft versus host disease (GVHD) is still the most important cause of mortality and morbidity after allogeneic stem cell transplantation. Though perfect response rates are not achieved, steroids are still the first-line treat-ment. In the face of the presence of the drugs approved by FDA in recent years for acute and chronic GVHD as second-line therapy in the steroid-refractory group, there exists no standard approach. Extracorporeal photopheresis (ECP) with an immunomodulatory effect, is favored in the treatment of both acute and chronic steroid refractory GVHD as it does not increase the risk of relapses or infections. Having a low profile of side effects, ECP is also generally well-tolerated by patients. Being a time requiring procedure, the fact is that it is not able to be practiced in all health centers and requires central venous catheters in patients unfit for venous access may be enumerated among its shortcomings. No complete standard is available with respect to ECP application frequency-time; it varies from one center to another. The Turkish Society of Apheresis established the Turkish ECP (TECP) group and sought some answers to the questions regarding the use of ECP in the treatment of GVHD, and issued a position statement.
Keywords: Acute Graft Versus Host Disease; Chronic Graft Versus Host Disease; Extracorporeal Photopheresis